Od "ta onta" do "to on" – mitologiczne źródła greckiego pojęcia bytu - Krajewski, Patryk (Acta Universitatis Lodziensis. Folia Philosophica. Ethica-Aesthetica-Practica, 2011)
The paper deals with the mythological background for the philosophical concept of being. Againstthis background the early development of this concept and its conditions are shown. Also, someattention will be paid to certain linguistic aspect behind this process.